Objective tests and the assessment of the acoustic properties of ear-plugs - Kotarbińska, E.; Kozłowski, E.; Młyński, R. (Archives of Acoustics, 2006)
Ear-plug-type hearing protectors are commonly used in a noisy working environment. Ina certification process of ear-plugs only sound attenuation is tested subjectively. There is norequirement of maximum variability in ear-plug insertion loss measured objectively like therequirement of maximum variability in ear-muff insertion loss. The aim of this paper is topresent the methodology and the results of insertion loss measurements for ear-plugs. Themeasurements were carried out in the laboratory test site meeting EN 24869-3 requirements,for test signals consisting of pink noise filtered through one-third octave bands with centrefrequencies of 63–8000 Hz, with a newly designed acoustic test fixture. Twenty popular modelsof ear-plugs (made of foam and cotton wool), with twenty samples of each model, weretested according to the worked out procedure. The mean values of insertion loss and standarddeviations for each frequency band of tested ear-plugs are presented.